PENGARUH MODAL SENDIRI DAN VOLUME USAHA TERHADAP SISA HASIL USAHA PADA KOPERASI SAWIT USAHA MAJU DESA MEKAR JAYA KECAMATAN KAMPAR KIRI TENGAH - Eka Sari Ramadhani; Ruzikna " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This study aims to test partially and simultaneously the effect of own capital and Business Volume on Net Income.Independent variables in this study are own capital and Business Volume and dependent variable is Net Income. This study uses secondary data in the form of company financial reports at Koperasi Sawit Usaha Maju. The data analysis use simple linear regression analysis, multiple linear regression, T test, F test and coefficient of determination test using SPSS 23 devices. The results show that the variable own capital partially (t test) influences the Net income, the business volume variable partially (t test) influences the Net income. Simultaneous test results (f test) indicate the influence of variable own capital and business volume in Koperasi Sawit Usaha Maju kecamatan Kampar Kiri Tengah.   Keywords: Own Capital, Business Volume and Net Imcome